Recent changes of the thermal structure in Three Gorges Reservoir, China and its impact on algal bloom in tributary bays. (November 2022) - Long, Lianghong; Chen, Peng; Xu, Hui; Ji, Daobin; Liu, Liu; Yang, Zhengjian; Lorke, Andreas
Graphical abstract: Highlights: A significant change in the thermal regime of Three Gorges Reservoir has been observed after two newly upstream-located reservoirs operated. Spring stratification in Three Gorges Reservoir became weaker and less frequent. The development of thermal stratification in Three Gorges Reservoir was closely related to discharge and water residence time. Reservoir warming can alter the hydrodynamics and water quality in tributary bays. Abstract: Despite the fact that the water temperature of the Yangtze River has changed substantially due to the construction of Three Gorges Reservoir (TGR), little is known about how the thermal structure of TGR responded to the implementation of two large upstream reservoirs in 2013. We investigated the seasonal variations of water temperature and discharge in the middle reaches of the Yangtze River by analyzing multi-year (2004–2018) hydrological and water temperature data. The effects of upstream dams on the thermal regime, density currents and phytoplankton blooms in TGR were examined. The results show that water temperature in TGR increased in spring (+1.1 °C) and winter (+0.8 °C) seasons after the filling of upstream reservoirs compared to the years before. Longer duration of stratification is associated with a smaller discharge and a longer water residence time. Moreover, the increase of inflow, which was at least partially due to upstream dam construction, lead to the weakening of stratification during the spring season. As a consequence of the higher water temperature in TGR in spring, the density-driven exchange flows between the main reservoir and tributary bays have changed. Overflows became more frequent, which promoted the deepening of the surface mixing layer, and resulted in a dramatic reduction in the frequency and biomass of phytoplankton blooms in tributary bays of TGR.